2016
DOI: 10.1016/j.celrep.2015.12.027
|View full text |Cite
|
Sign up to set email alerts
|

ECM Signaling Regulates Collective Cellular Dynamics to Control Pancreas Branching Morphogenesis

Abstract: Summary During pancreas development, epithelial buds undergo branching morphogenesis to form an exocrine and endocrine gland. Proper morphogenesis is necessary for correct lineage allocation of pancreatic progenitors; however, the cellular events underlying pancreas morphogenesis are unknown. Here, we employed time-lapse microscopy and fluorescent labeling of cells to analyze cell behaviors associated with pancreas morphogenesis. We observed that outer bud cells adjacent to the basement membrane are pleomorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
96
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(102 citation statements)
references
References 29 publications
5
96
1
Order By: Relevance
“…In contrast, mammalian epithelial branching organs undergo collective migration in the absence of these invasive leading-edge membrane protrusions (Ewald et al, 2008;Schnatwinkel and Niswander, 2013). Live imaging of the salivary gland (Hsu et al, 2013;Larsen et al, 2006), lung (Schnatwinkel and Niswander, 2013), kidney (Riccio et al, 2016), mammary gland (Huebner et al, 2016) and pancreas (Shih et al, 2016) have all revealed that the peripheral bud tip cells in these organs are more dynamic compared with inner bud and ductal cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, mammalian epithelial branching organs undergo collective migration in the absence of these invasive leading-edge membrane protrusions (Ewald et al, 2008;Schnatwinkel and Niswander, 2013). Live imaging of the salivary gland (Hsu et al, 2013;Larsen et al, 2006), lung (Schnatwinkel and Niswander, 2013), kidney (Riccio et al, 2016), mammary gland (Huebner et al, 2016) and pancreas (Shih et al, 2016) have all revealed that the peripheral bud tip cells in these organs are more dynamic compared with inner bud and ductal cells.…”
Section: Discussionmentioning
confidence: 99%
“…In salivary gland and pancreas, integrin-mediated signaling from the basement membrane appears to maintain enhanced velocity or directionality of outer bud cell migration (Hsu et al, 2013;Shih et al, 2016). Inhibition of integrin signaling switches the migratory behavior of outer cells to resemble the inner cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beginning at E10.75, microlumen structures begin to form, with cells establishing an apical polarity eventually leading to duct formation (83). Integrin-based interactions between outer cells of the developing buds and the adjacent basement membrane are required for initiation of branching (149). Minimal expression of pancreatic hormones and digestive enzymes is observed, although endocrine cells expressing multiple hormones exist, present as clusters within the dorsal bud.…”
Section: Morphological Developmentfrom Endoderm To Definitive Pancreasmentioning
confidence: 99%